INTEGRITAS BERPERILAKU KUDUS BERDASARKAN 1 PETRUS 1:13-25 TERHADAP KOMITMEN PELAYANAN PADUAN SUARA ADONAI - Frieska Putrima Tadung (Sekolah Tinggi Teologi Excelsius, 2020)
Integrity to behave holy is a life that shows as befits the family of God, which is to live a life that matches the calling. A life that should be